Preparing the Gut with Antibiotics Enhances Gut Microbiota Reprogramming Efficiency by Promoting Xenomicrobiota Colonization - Ji, Shou K.; Yan, Hui; Jiang, Tao; Guo, Chun Y.; Liu, Jing J.; Dong, Shuang Z.; Yang, Kai L.; Wang, Ya J.; Cao, Zhi J.; Li, Sheng L. (Frontiers in Microbiology, 2017)
Gut microbiota plays multiple important roles in intestinal and physiological homeostasis, and using fecal microbiota transplantation (FMT) to reprogram gut microbiota has demonstrated promise for redressing intestinal and physiological disorders. This study tested the alterations in reprogramming efficiency caused by different gut preparation procedures and explored the associated underlying mechanisms. We prepared the guts of mice for FMT by administering one of the three most-clinically used pretreatments [antibiotics, bowel cleansing (BC) solution, or no pretreatment], and we found that preparing the gut with antibiotics induced a more efficient modification of the gut bacterial community than was induced by either of the other two pretreatment types. The increased efficiency of antibiotic treatment appeared to occur via increasing the xenomicrobiota colonization. Further analysis demonstrated that antibiotic treatment of mice induced intestinal microbiota disruption, mostly by expelling antibiotic-sensitive bacteria, while the indigenous microbiota was maintained after treatment with a BC solution or in the absence of pretreatment. The amount of antibiotic-resistant bacteria increased shortly after antibiotics usage but subsequently decreased after FMT administration. Together, these results suggest that FMT relied on the available niches in the intestinal mucosa and that preparing the gut with antibiotics facilitated xenomicrobiota colonization in the intestinal mucosa, which thus enhanced the overall gut microbiota reprogramming efficiency.